My watch list
my.chemeurope.com

# Hypsometric equation

The hypsometric equation relates the atmospheric pressure ratio to the thickness of an atmospheric layer under the assumptions of constant temperature and gravity. It is derived from the hydrostatic equation and the ideal gas law.

It is expressed as:

$\ h = z_2 - z_1 = \frac{R \cdot T}{g} \cdot \ln \left [ \frac{P_1}{P_2} \right ]$

where:

$\ h$ = thickness of the layer [m]
$\ z$ = geopotential height [m]
$\ R$ = gas constant for dry air
$\ T$ = temperature in kelvins [K]
$\ g$ = gravitational acceleration [m/s2]
$\ P$ = pressure [Pa]

In meteorology P1 and P2 are isobaric surfaces and T is the average temperature of the layer between them. In altimetry with the International Standard Atmosphere the hypsometric equation is used to compute pressure at a given geopotential height in isothermal layers in the upper and lower stratosphere.

## Derivation

The hydrostatic equation:

$\ P = \rho \cdot g \cdot z$

where $\ \rho$ is the density [kg/m3], is used to generate the equation for hydrostatic equilibrium, written in differential form:

$dP = - \rho \cdot g \cdot dz.$

This is combined with the ideal gas law:

$\ P = \rho \cdot R \cdot T$

to eliminate $\ \rho$:

$\frac{\mathrm{d}P}{P} = \frac{-g}{R \cdot T} \, \mathrm{d}z.$

This is integrated from $\ z_1$ to $\ z_2$:

$\ \int_{p(z_1)}^{p(z_2)} \frac{\mathrm{d}P}{P} = \int_{z_1}^{z_2}\frac{-g}{R \cdot T} \, \mathrm{d}z.$

Integration gives:

$\ln \left( \frac{P(z_2)}{P(z_1)} \right) = \frac{-g}{R \cdot T} ( z_2 - z_1 )$

simplifying to:

$\ln \left( \frac{P_1}{P_2} \right) = \frac{g}{R \cdot T} ( z_2 - z_1 ).$

Rearranging:

$( z_2 - z_1 ) = \frac{R \cdot T}{g} \ln \left( \frac{P_1}{P_2} \right)$

or, eliminating the logarithm:

$\frac{P_1}{P_2} =e ^ { {g \over R \cdot T} \cdot ( z_2 - z_1 )}.$

## References

• AMS Glossary of Meteorology